Analisis Hukum Tentang Tanggung Jawab Pemerintah Dalam Mengamankan Pertandingan Sepakbola: Kasus Tragedi Kanjuruhan 2022 - Tristan Cakra Permana; Firdaus Arifin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Kanjuruhan Tragedy on October 1, 2022, at Kanjuruhan Stadium, Malang Regency, represents one of the deadliest incidents in Indonesian football history, resulting in the death of over 130 spectators and injuries to hundreds of others. This study examines the legal responsibility of the government and local authorities in ensuring security and protecting human rights during football events, based on the principles of state accountability and authority. The research employs a normativeempirical legal approach, utilizing primary data from official reports of Komnas HAM, statements from the police and local government, and existing football safety regulations, as well as secondary data from relevant laws, journals, and academic literature. The study concludes that reform in regulatory frameworks, standardized safety protocols, and stronger oversight mechanisms are urgently needed to prevent similar tragedies and to ensure that government authorities uphold their duty of care in sporting events.